Catalytic oxidation of toxic organics in aqueous solution for wastewater treatment: a review - Saputra, Edy; Utama, P.; Muhammad, Syaifullah; Ang, Ha Ming; Tade, Moses; Wang, Shaobin (Songkla University, 2011)
The paper reviews catalytic oxidation for the treatment of wastewater that contains toxic organics from industry or domestics which have to be treated before returning into the aquatic environment. Conventional or individual wastewater treatment often cannot degrade organic compounds completely. Therefore, advanced wastewater treatment process is needed, which combines several methods such as catalyst, oxidant and photocatalytic. From the previous studies, advanced process proved to improve the degradation efficiency of organic pollutants from the effluents.